A generalized technique for the encapsulation of nano‐sized NiO particles by styrene‐2‐hydroxyethyl methacrylate copolymer. (29th April 2015) - Hossan, M. Shamim; Rahman, M. Abdur; Tauer, Klaus; Minami, Hideto; Ahmad, Hasan
<x xml:space="preserve">Abstract</x> Encapsulation of nickel oxide (NiO) particles is of great interest to the researchers as such modification produces remarkable improvement in properties and versatility in application potential. In this investigation, nanosized NiO particles were first prepared by calcination of nickel hydroxide precursor obtained using a simple liquid‐phase process. The produced NiO particles were stabilized with oleic acid and then treated with tetraethylorthosilicate to produce NiO/SiO2 composite seed particles. Finally tri‐layered inorganic/organic composite particles were prepared by seeded copolymerization of styrene and 2‐hydroxyethyl methacrylate (HEMA) in the presence of NiO/SiO2 composite seed particles. The produced composite particles named as NiO/SiO2/P(S‐HEMA) were colloidally stable, and the obtained particles were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, X‐ray diffraction, X‐ray photoelectron spectroscopy and thermogravimetric analyses. Copyright © 2015 John Wiley & Sons, Ltd.